2009
DOI: 10.7589/0090-3558-45.2.375
|View full text |Cite
|
Sign up to set email alerts
|

Animal Rabies in Massachusetts, 1985–2006

Abstract: ABSTRACT:In this study, we review annual rabies data from Massachusetts from 1985 to 2006, spanning the introduction of raccoon strain rabies in 1992. Of 52,034 animals tested, 9.7% (5,049/ 52,034) were rabid, representing 26 of over 67 species submitted. Bats were the most common rabid animals prior to 1992 (50 of 52), but raccoons (Procyon lotor) became the most common rabies-positive species upon arrival of raccoon strain rabies virus (38.2%, 2,728 of 7,138 tested), followed by striped skunks (Mephitis meph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
(33 reference statements)
1
3
0
Order By: Relevance
“…These findings are supported by limited laboratory typing data in rabid bats, which showed no evidence that RRV plays a role in bat infection. This finding is consistent with reports that insectivorous bat rabies virus variants circulate separately from terrestrial viral variants ( 9 , 10 ). Although incidents of bat rabies virus variant spillover into terrestrial mammals are documented ( 11 ), spillover of terrestrial variants into bats has yet to be reported.…”
Section: Discussionsupporting
confidence: 93%
“…These findings are supported by limited laboratory typing data in rabid bats, which showed no evidence that RRV plays a role in bat infection. This finding is consistent with reports that insectivorous bat rabies virus variants circulate separately from terrestrial viral variants ( 9 , 10 ). Although incidents of bat rabies virus variant spillover into terrestrial mammals are documented ( 11 ), spillover of terrestrial variants into bats has yet to be reported.…”
Section: Discussionsupporting
confidence: 93%
“…Wild carnivores are natural reservoirs (Faber et al 2009) and are responsible for the maintenance of the infectious cycle. Despite most of the wildlife species carry their own rabies variant, the spillover to other species is possible (Lackay et al 2008;Wang et al 2009). In Europe, urban dog rabies has been largely eliminated, and the main wildlife reservoir is the red fox (Vulpes vulpes) (Kuzmin et al 2004).…”
Section: Viral Diseasesmentioning
confidence: 98%
“…The introduction of raccoon rabies variant (RRV) in Massachusetts in September 1992, resulted in an enormous and sustained increase in rabies cases among terrestrial animals [ 1 ]. While this dramatic shift in the incidence and epidemiology of animal rabies in MA has been well-characterized, questions remain regarding clinical features among individual animal species infected with the new virus variant.…”
Section: Introductionmentioning
confidence: 99%